Fundamentals of biology - Formacion, Minda J.; Geduspan, Jane S.;Gacutan, Ma. Vicenta C.;Katalbas, Ma. Severa Fe S. (Manila, Philippines : Rex Book Store, 2011)
Biology is a fast advancing field of study with new interesting discoveries, especially in the field of cell and molecular biology. Therefore, the understanding of the basic concepts in biology is necessary to disseminate the information to students and to the general public.
Chapter 1. Introduction: Science of Life -- Chapter 2. Cell Structure -- Chapter 3. Tissues -- Chapter 4. Organ Systems -- Chapter 5. Reproduction and Development -- Chapter 6. Patterns of Heredity -- Chapter 7. Biological Diversity -- Chapter 8. Ecology.
Includes bibliographical references and index.
Keywords: BIOLOGY -- SCIENCE